Application of B-trees for Design of Optimal Page Replacement Technique in Modern Operating Systems - Sai Ganesh Palli; Manas Kumar Yogi (International Journal of Data Structure Studies, 2025)
Algorithms related to replacing the memory pages in operating systems are critical components of modern operating systems that manage virtual memory efficiently. Current algorithms such as LRU (Least Recently Used), Clock algorithms as well as FIFO (First-In-First-Out), often struggle with the increasing demands of contemporary applications and larger memory hierarchies. This research work proposes a novel approach utilizing B-tree data structures to design an optimal page replacement technique. The proposed methodology leverages the inherent properties of B-trees: balanced structure, logarithmic search time, and efficient insertion/deletion operations, to maintain temporal and spatial locality information. Our analysis demonstrates that B-tree-based page replacement can achieve superior performance in terms of page fault rates, search efficiency, and adaptability to varying workload patterns. This study presents the theoretical foundation, algorithm design, performance analysis, and comparative evaluation with existing techniques, providing insights into the practical implementation of B-trees for memory management in modern operating systems.
Keywords: B-trees; cache optimization; memory management; operating systems; page replacement; virtual memory